Type VIII collagen: advances in matrix biology and translational promise - Shi, Haiyan; Yu, Yufeng; Guo, Kaixuan; He, Rongli (Frontiers in Bioengineering and Biotechnology, 2026)
Type VIII collagen, a member of the short-chain collagen family, plays essential roles in structural support, functional regulation, and mechanobiology across multiple organ systems. Although early studies suggested ubiquitous expression, emerging single-cell transcriptomic and proteomic analyses have refined this view, demonstrating selective enrichment in corneal endothelial cells, vascular smooth muscle cells, activated fibroblasts, and tumor-associated extracellular matrix (ECM) compartments. These findings establish type VIII collagen as both a structural constituent of the ECM and a dynamic regulator of cell behavior. Functionally, type VIII collagen is critical for endothelial cell stability, angiogenesis, ECM remodeling, and mechanosignaling. Dysregulation of Col8a1 and Col8a2 is implicated in a broad spectrum of disorders, including vascular remodeling, tissue fibrosis, diabetic nephropathy, cancer progression, and corneal endothelial dystrophies. With growing mechanistic insight, translational applications are rapidly expanding. Current directions include gene-editing strategies targeting Col8a2 for Fuchs’ endothelial corneal dystrophy, RNA-based approaches to dissect Col8a1and Col8a2 regulation in fibrotic and vascular disease, and the development of biomaterials incorporating type VIII collagen–derived motifs to promote endothelial repair and guide angiogenesis. Moreover, its restricted expression profile supports its potential utility as a diagnostic and prognostic biomarker. Collectively, these advances position type VIII collagen as a multifunctional ECM regulator with substantial promise for disease diagnostics, therapeutic innovation, and biomaterial engineering.